Do blood flow patterns in the left atriums differ between left upper lobectomy and other lobectomies? A computational study - Yi, Wentao; Otani, Tomohiro; Endo, Shunsuke; Wada, Shigeo (Frontiers in Cardiovascular Medicine, 2024)
Background: Left atrial (LA) hemodynamics after lung lobectomies with pulmonary vein (PV) resection is widely understood to be a risk factor for LA thrombosis. A recent magnetic resonance imaging study showed that left upper lobectomy (LUL) with left superior pulmonary vein resection tended to cause LA flow patterns distinct from those of other lobectomies, with flow disturbances seen near the PV stump. However, little is known about this flow pattern because of severe image resolution limitations. The present study compared flow patterns in the LA after LUL with the flow patterns of other lobectomies using computational simulations. Methods: The computational simulations of LA blood flow were conducted on the basis of four-dimensional computed tomography images of four lung cancer patients prior to lobectomies. Four kinds of PV resection cases were constructed by cutting each one of the PVs from the LA of each patient. We performed a total of five cases (pre-resection case and four PV resection cases) in each patient and evaluated global flow patterns formed by the remaining PV inflow, especially in the upper LA region. Results: LUL tended to enhance the remaining left inferior PV inflow, with impingements seen in the right PV inflows in the upper LA region near the PV stump. These flow alterations induced viscous dissipation and the LUL cases had the highest values compared to other PV resection cases, especially in the LV systole in three patients, and reached three to four times higher than those in pre-resection cases. However, in another patient, these tendencies were weaker when PV inflow was stronger from the right side than from the left side, and the degree of flow dissipation was lower than those in other PV resection cases. Conclusion: These findings suggest marked variations in LA flow patterns among patients after lobectomies and highlights the importance of patient-specific assessment of LA hemodynamics after lobectomies.